Influence of recycle streams of C5/C6 and C4 hydrocarbon cuts on the performance of methanol to propylene (PVM) reactors. (23rd November 2017) - Kazemi, Abolghasem; Beheshti, Masoud; Khalili, Reza
Highlights: Effects of operating parameters are investigated on methanol to propylene reaction. C5 /C6 and C4 hydrocarbon cuts are co fed to the reactors. Effects of co feeding hydrocarbon cuts on product distribution are investigated. Conditions of steady state recycle streams of hydrocarbon cuts are determined. Abstract: Conversion of methanol to propylene combined with cracking of C5 /C6 and C4 hydrocarbon cuts was studied on a commercial Süd-Chemie Germany ZSM-5 catalyst. The C5 /C6 hydrocarbon cut consisted of hydrocarbons with 5 and 6 carbons in their structure (27.74% i-pentene, 43.14% i-hexene, 3.70% i-pentane and 7.37% i-hexane). The C4 hydrocarbon cut consisted of both olefinic and paraffinic molecules. A fraction of the feed hydrocarbon mixture was converted to other hydrocarbons while the conversion of methanol was remained close to 100%. It was observed that co feeding of the hydrocarbons mixture with methanol considerably increase propylene selectivity. Propylene selectivity up to 61% was gained in the propylene via methanol (PVM) process by co feeding of C5 /C6 hydrocarbon cuts. For the C4 hydrocarbon cut, propylene selectivity up to 65% was obtained. However, these values do not represent the actual selectivity at actual flow rates of recycle streams. Based on third order polynomials, effects of steady state recycle streams of these cuts are also predicted in this paper. At the best conditions of a steady state recycle stream, 47.7% selectivity was obtained for propylene in the PVM reactors.